Development and delivery of an interdisciplinary course for nursing and office administration - White , Allison; Miller , Char (Journal of Interdisciplinary Studies in Education, 2014)
The development of an interdisciplinary course is a process derived from a unique educational or workplace need.  The course can create a logical link between two or more programs with a career-based outcome that is invaluable to the graduate seeking employment.  The process of creating, delivering, and revising an interdisciplinary course for nursing, office administration, and related majors (i.e. health services administration, human services technology, and medical assisting) is described in this manuscript.  Important components of interdisciplinary course development and the highly technical, collaborative teaching environment are explained along with students’ perceptions and recommendations which provide the basis for refinement.